A força crítica da reflexão kantiana e a possibilidade de suautilização na crítica da arte contemporânea - Hudson de Oliveira Assis (2016)
With the expansion of the frontiers, the questioning and the constant reinvention of art, increasingly seems to require the viewer an active role, we would like to call "critical." The hypothesis of this paper is that perhaps the Kantian notion of reflection can provide a foundation for this critical attitude. In other words, it defends the vitality of Kantian aesthetics for the treatment of new questions about art today. It has been proven the hypothesis that the critique of contemporary art can be founded by approach and analogy in Kant's aesthetic reflection, then the judgment of taste, according to Kant, should provide us with an answer to the question about the critical conditions of possibility of contemporary art. The American philosopher of art, Arthur Danto, considered a possible day comes to a philosophical concept art. Thesis with which we disagree or at least are skeptical about this possibility. We therefore believe that the only way to approach contemporary art is the approach "subjective", since we always just missing one's philosophical concept art! Instead of seeking a more consistent definition of art, this research was restricted to unique ability to make a judgment. Here, we call this judgment "critical judgment". And the task that this Dissertation was proposed to seek its foundation or essence precisely in freedom and autonomy. And so it was essential to examine the reflective attitude of the viewer about his own subjective state of mind. We perform an exegesis of the first part of the judgment College of Critical which can be characterized as the main work of Kantian aesthetics. Then relying on useful analysis that made art Danto in our time, we outlined the objective conditions (which is different from a concept) of contemporary art. On the other hand, against him relate those objective conditions of art to the contributions of Kantian aesthetics, and affirming its relevance, it tried to find the foundations of the critique of contemporary art.